HUBUNGAN OBESITAS TERHADAP HIPERTENSI GESTASIONAL PADA IBU HAMIL DI WILAYAH KERJA UPT. PUSKESMAS SEKUPANG KOTA BATAM - Maulinda Aryani; Norma Jeepi Margiyanti, Huzaima (CV. Adiba Aisha Amira, 2024)
In Indonesia, the Maternal Mortality Rate (MMR) is still relatively high. Hypertension It often occurs in pregnancy and is one of the causes of maternal death. In Indonesia, hypertension in pregnancy is ranked third highest The cause of death was hemorrhage. Hypertension in pregnancy occurs due to various factors, namely age, parity, gravidity, weight gain (obesity). This study aims to determine the relationship between obesity and gestational hypertension in pregnant women di Wilayah Kerja UPT. Puskesmas Sekupang Kota Batam 2023. This research design uses analytical observational with a cross sectional design. The respondents in this study were 62 pregnant women. The sampling technique used was purposive sampling. The chi square statistical test results show p-value = 0.000 (<0.05) so that Ho is rejected and Ha is accepted. This shows that there is a relationship between obesity and gestational hypertension in pregnant women di Wilayah Kerja UPT. Puskesmas Sekupang Kota Batam 2023. The conclusion of this research is that obese pregnant women can cause hypertension in pregnancy. It is recommended for pregnant women to adopt a healthy lifestyle such as light exercise, a healthy diet, and relaxation to prevent hypertension in pregnancy.